1984
DOI: 10.1159/000215088
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Exchange between Blood and in vitro Thrombi

Abstract: Uptake of radioiodinated Lys-plasminogen (125I-PLG), albumin (125I-ALB), and tritiated water (3H-H2O) by in vitro thrombi and interchange of these molecules with blood in an in vitro perfusion system were investigated. The radioisotopes were taken up by thrombi either by incorporation during formation in radiolabelled blood or by perfusion of preformed nonradioactive thrombi in radiolabelled blood. Release of the radioisotopes into a perfusion medium of nonradiolabel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1985
1985
2001
2001

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…It can no longer be characterized solely in terms of intrinsic or extrinsic lysis, but rather as an intricate set of interactions, involving both a liquid medium and a solid, yet perme able, thrombus that can exchange substances with the medium in which it is perfused [15]. Based on the results of the present study, it is concluded that in a blood-thrombus biphasic thrombolytic system induced by UK, there is interaction between the phases, and that PLG in both phases influences thrombolysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can no longer be characterized solely in terms of intrinsic or extrinsic lysis, but rather as an intricate set of interactions, involving both a liquid medium and a solid, yet perme able, thrombus that can exchange substances with the medium in which it is perfused [15]. Based on the results of the present study, it is concluded that in a blood-thrombus biphasic thrombolytic system induced by UK, there is interaction between the phases, and that PLG in both phases influences thrombolysis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the predom inantly solid thrombus is permeable to plasma so that the liquid phase extends into the interstitial compartment of the thrombus thereby linking the interior of the thrombus with the surrounding liquid perfusion me dium. In a previous study [15] it was shown that radiolabclled plasminogen (PLG), albu min and water may diffuse into an in vitro thrombus from the surrounding plasma me dium and out again. Thus, there is, in fact, interchange of plasma constituents between the internal milieu of an in vitro thrombus and the external milieu of plasma that bathes it.…”
Section: Introductionmentioning
confidence: 99%